SIKAP KONFORMITAS MAHASISWA DALAM MENGGUNAKAN MASKER PADA ERA PANDEMI - Suci Hayatullah; Hesti Asriwandari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Student Conformity In Using Masks In The Pandemic Era. This research was conducted at the University of Riau. The porpose of this study was to determine the level of student conformity in using masks during a pandemic. The focus topic of this research is the attitude of students in using masks during the pandemic. The data analysis in this study was using descripstive quantitative methods, which involved students’ attitude in using masks. The formulation of the problem in this study (1) How is the attitude of conformity of students in using masks? (2) How do cognitive and affective factors affect students' conformity in using masks?. The data collection technique in this study was in the form of a questionnaire distributed online using a google form. The sample in this study amounted to 100 people who were determined using the slovin formula. The data analysis technique in this study is quantitative descriptive using SPSS version 24. The results of this study explain the level of conformity of students in using masks is at a high level, which is measured by 5 indicators including using masks during a pandemic at home, wearing masks when leaving the house, caring in wearing masks, socializing the use of masks and participating as volunteers. Cognitive and affective factors of students in using masks are also at a high level. Keywords: conformity attitude, college student, pandemic.